International Journal of Environmental Research - Ardestani, Mojtaba; Niksokhan, Mohammad H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
International Journal of Environmental Research is a multidisciplinary journal concerned with all aspects of environment. In pursuit of these, environmentalist disciplines are invited to contribute their knowledge and experience. International Journal of Environmental Research publishes original research papers, research notes and reviews across the broad field of environment. These include but are not limited to environmental science, environmental engineering, environmental management and planning and environmental design, urban and regional landscape design and natural disaster management. Thus high quality research papers or reviews dealing with any aspect of environment are welcomed. Papers may be theoretical, interpretative or experimental.
Keywords: Natural disasters; Regional planning; Urban planning; Environmental management; Geoecology; Environmental geology; Environmental engineering; Biotechnology; Environmental Management; Environmental Engineering/Biotechnology.; Geoecology/Natural Processes; Natural Hazards; Landscape/Regional and Urban Planning